PEMBINAAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA SISWA SDN TLOGOMAS 2, KOTA MALANG - Wibisono, Nugroho; Najah, Jafnin; Wulan Sari, Mutiara Nur; Pramadani, Iqbal; Ricky Purnama, Kurniawan (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Schools not only function as a place for learning, but also as a place to introduce clean and healthy living behavior, especially for elementary school level children. Clean and healthy living behavior (PHBS) is one of the fundamental human rights, which plays an important role in maintaining the health and survival of individuals. In this context, counseling on PHBS becomes very important. For example, through activities such as counseling on how to wash hands properly, children are not only taught techniques, but also understand the importance of cleanliness to prevent disease. This study used a comparative analytical method with a single-group pretest and posttest design. Before the counseling, the pretest results showed that 15% of children did not understand the concept of PHBS, while 85% already had sufficient understanding. However, after the counseling, the posttest results showed a significant result 95.83% of children understood the importance of PHBS, while only 4.17% still did not understand. This change not only shows the effectiveness of the counseling, but also illustrates how the information conveyed can be absorbed into children's understanding. From the results above, it can be concluded that with counseling, knowledge about PHBS in schools can increase significantly. This shows that schools have a very vital role in shaping healthy behavior among children, which in turn can contribute to overall public health. Thus, it is important for educational institutions to continue to integrate health programs into their curriculum, so that children can grow into a generation that is not only smart, but also healthy. --- Sekolah tidak hanya berfungsi sebagai tempat untuk proses belajar, tetapi juga sebagai wadah untuk memperkenalkan perilaku hidup bersih dan sehat, khususnya bagi anak-anak di tingkat sekolah dasar. Perilaku hidup bersih dan sehat (PHBS) merupakan salah satu hak asasi manusia yang fundamental, yang berperan penting dalam menjaga kesehatan dan kelangsungan hidup individu. Dalam konteks ini, penyuluhan mengenai PHBS menjadi sangat penting. Misalnya, melalui kegiatan seperti penyuluhan tentang cara mencuci tangan yang benar, anak-anak tidak hanya diajarkan teknik, tetapi juga memahami pentingnya kebersihan untuk mencegah penyakit. Penelitian ini menggunakan metode analitik komparatif dengan rancangan satu kelompok pretest dan posttest. Sebelum penyuluhan, hasil pretest menunjukkan bahwa 15% anak belum memahami konsep PHBS, sementara 85% sudah memiliki pemahaman yang cukup. Namun, setelah dilakukan penyuluhan, hasil posttest menunjukkan hasil yang signifikan 95,83% anak paham akan pentingnya PHBS, sedangkan hanya 4,17% yang masih belum paham. Perubahan ini tidak hanya menunjukkan efektivitas penyuluhan, tetapi juga menggambarkan bagaimana informasi yang disampaikan dapat meresap ke dalam pemahaman anak-anak. Dari hasil diatas dapat disimpulkan bahwa dengan adanya penyuluhan, akan meningkatkan pengetahuan dan kesadaran pada peserta didik akan pentingnya pola hidup bersih dan sehat.